1983
DOI: 10.3382/ps.0622073
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Levels of Fat, Calcium, and Vitamins A and D3 as Contributory Factors to Rickets in Poults

Abstract: Two experiments were conducted on dietary predisposition to rickets in poults. The first experiment compared fat type (corn oil or tallow), level of added fat (3.5 or 7%), vitamin D3 (900 or 2,400 IU/kg feed), and total calcium (.6, 1.2, or 3%) inclusion in the diet. Poults fed diets supplemented with corn oil had higher percentage tibia ash than poults fed tallow-supplemented diets. Vitamin D3 included at 2,400 IU/kg feed increased body weights significantly by 2 and 4 weeks of age and lowered plasma alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The one exception to this was the ash content at 21 days of age. Stevens et al (1983) also found that diets containing 7% tallow reduced tibial ash in turkey poults at 3 weeks of age.…”
Section: Discussionmentioning
confidence: 90%
“…The one exception to this was the ash content at 21 days of age. Stevens et al (1983) also found that diets containing 7% tallow reduced tibial ash in turkey poults at 3 weeks of age.…”
Section: Discussionmentioning
confidence: 90%
“…At the end of the 4-week test period, six females from each treatment (one per pen) were killed and the left tibiae excised for bone ash determination as described by Stevens et al (1983).…”
Section: Methodsmentioning
confidence: 99%
“…Poorer fat digestion at an early age could limit the absorption of fat soluble vitamins, especially cholecalciferol (vitamin D 3 ), at 877 878 V. I. STEVENS AND R. E. SALMON a time when poults are susceptible to rickets. Previous studies have also shown that excess dietary retinol (vitamin A) may interfere with absorption and/or metabolism of cholecalciferol and result in increased incidence of leg problems in turkeys (Stevens et al, 1983;Metz et al, 1985;and Veltmann et al, 1987).…”
Section: Introductionmentioning
confidence: 93%